2011
DOI: 10.1038/pr.2011.1049
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding Problems During First Three Postnatal Days

Abstract: Background and aims:We surveyed late preterm and term mother-newborn dyads (n=380) in a tertiary care hospital to determine the epidemiology of breastfeeding problems during initial 72 hours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…An All India Institute of Medical sciences study had more reported as well as observed problems. This may be attributed to the difference in sample size and other demographic variations [6].…”
Section: Discussionmentioning
confidence: 99%
“…An All India Institute of Medical sciences study had more reported as well as observed problems. This may be attributed to the difference in sample size and other demographic variations [6].…”
Section: Discussionmentioning
confidence: 99%